The Kurdish Armed Struggle in Turkey and the Scope of International Law (Raparin Journal of Humanities (RJH), 2023)
The Kurdish issue is one of the complex issues in the Middle East region that has along bloody history. Although the issue is originally related to the sovereignty of the Kurds over their historical land, the geopolitical changes has transformed it into the question of identity and group rights in the states into which they are divided. Turkey is one of the region’s new states where the majority of Kurds reside in today but the state denies their distinct ethnic identity in its constitution and laws and they have consequently been deprived of all collective civil and political rights in the form of democratic autonomy. Meanwhile, the Kurds have a distinct historical tradition, cultural homogeneity, linguistic unity and territorial connection which ultimately make them qualify as a people and according to modern international law, all peoples have the right to self-determination at least in an internal context. In contrast to the state denial and tyrannical policy, the Kurds have not kept their silence but resisted the state. In their resistance, they have tried to resort to peaceful means in the form of demands and agreements and in contemporary times through political and civil parties and organizations but the state has not and does not allow such a movement. This article attempts to illustrate the origins of the issues which are rights and freedoms of the Kurds on the bases of a discriptive analytical method, alongside the recognition of the Kurdish struggle in Turkey as terrorism by the international community under the influence of Turkish media and diplomacy.